In Search of a New Approach for Urban Policies under Shrinkage Tendencies in Poland - Jaroszewska, Emilia (Journal of Tourism, Sustainability and Well-being, 2014)
The new demographic, social, economic and cultural conditions that appeared in Poland after 1990 have crucially influenced the transformation of its cities in both quantitative and qualitative terms. One of the manifestations of those changes is an increasingly visible process of shrinkage of many of them. The overcoming of its detrimental effects will be one of the most important challenges for planning and urban policy in Poland in the 21st century. This article seeks to identify new urban policy challenges that Polish cities have to meet in the face of advancing urban shrinkage. It starts with the presentation of theoretical issues concerning urban policy and urban shrinkage. Discussed next are the formation of urban policy in Poland and major aspects of the transformation and shrinkage of Polish cities after 1990. Special emphasis is put on the need to work out a new, integrated urban policy that would allow them to adapt to the negative demographic trends observed.